Aspectos adaptativos dos processos digestivo e metabólico de juvenis de pintado (Pseudoplatystoma corruscans) arraçoados com diferentes níveis de proteína e energia - Lundstedt, Lícia Maria (Universidade Federal de São Carlos, 2003)
The biological growth is reflected on metabolical adjustments, which are sustained by the nutritional status and is function of feeding. Pintado (Pseudoplatystoma corruscans) is a carnivorous fish appreciated by the fillet, in sportive fishing and presents good aquaculture potential, in spite of the rearing technology is not well established. This work aimed to study adaptive aspects of digestion, metabolic processes and intestinal morphology of juvenile pintado fed on different protein and energy levels. In the first set of experiments, fish were submitted to isoenergetic diets (4,000 kcal GE/kg) with different protein levels (20, 30 40 and 50% CP), and digestive enzymes, metabolites and intestine morphology were analyzed. In the second step, fish were submitted to isoproteic diets (31,5% CP) and different amounts of crude energy (3,500; 3,850 and 4,200 kcal GE/kg), and digestive enzymes and metabolites were analyzed. Crude extract from stomach, anterior, medium and posterior intestine were used to assay unspecific protease, trypsin, chymotrypsin, lipase and amylase. Blood was used to hematimetric analysis. Plasma, liver, white muscle and kidney samples were used to glucose, lactate, pyruvate, ammonia, urea (acid extracts), free amino acids, triglycerides, free fatty acids (neutral extracts), glycogen and total protein (alkaline extracts) determination; and assays of glutamate dehydrogenase plus arginase. The best weight gain percent was achieved by the fish fed on 40% CP followed by 30, 50 and 20% respectively. Fish fed lower amounts of energy (3,500 kcal/kg) reached weight gain higher than the other treatments. Metabolic profile was reflected in the fish yield and it was possible to verify through it that the poor as well as the richer diets in crude protein impaired the metabolism of pintado. Likely, the amount of essential amino acids were not supplied by the lower CP (20%), and the largest (50%) leaded to metabolical rearrangements as the neoglycogenesis to hold the glucemia and support energetic demands. Surplus of dietary energy probably leads the fish to decreasing of food intake and drives them to consuming the bulk of energetical molecules with consequent growth loss. The higher proteolytic activities were observed in stomach, where lipolytic and amylolytic activities were also detected. This fact highlights the role of that structure in the digestive processes of pintado. Proteolytic activities were not responsive to CP levels but supplying essential amino acids requirements as function of energetic demands. This picture suggests this group of enzymes is constitutive and allow us to assume the species is well fitted to utilize protein in spite of its dietary amount. Lipase also seems to be a constitutive enzyme, changing its activity just as function of food intake instead of diet lipid level. Amylase is less active in pintado than the most omnivorous species. Its activity, however seems to be function of the dietary glycogen content. Considering the lower digestive enzyme activities in the small intestine and its short size, it is reasonable to assume that the main role of such structure is the nutrient uptake. The histological analyzes strength that assumption, as the morphological responses are evidently adaptive to the CP dietary levels. The number of mucus producer cells (goblet cells) increased in consonance with the fold sizes and thickness of the muscularis, furthering the motility of the folds and optimizing the absorptive processes. The great variation of protein, lipid and carbohydrate here assayed allow us to assume that the optimizations of pintado diets are very dependent of the best ratios of them.
Keywords: Bioquímica; Bioquímica adaptativa; Pseudoplatystoma corruscans; Enzimas digestivas; Metabolismo; Aqüicultura; Nutrição de peixes; Morfologia; CIENCIAS BIOLOGICAS::BIOQUIMICA